The scandal of the Gospels : Jesus, story, and offense - McCracken, David (New York Oxford University Press, 1994)
This book argues that the gospels are in an important sense "occasions for offense." The Jesus of the gospels is a scandal (skandalon, in the original Greek) and he is never more scandalous than when he is speaking in parables. Interpreters of the gospels over the centuries have consistently labored to domesticate the offense or to eliminate it entirely. David McCracken, focusing on parables, Matthew's narrative contexts, and the gospel of John, seeks to recover the; gospels' sense of Jesus as skandalon. To this end, he enlists the help of Kierkegaard, the philosopher of offense, and to a lesser extent that of Bakhtin, both of whom prove to be surprisingly apt conversation partners for the evangelists.
Keywords: Jesus Christ -- Person and offices -- Biblical teaching. Kierkegaard, Søren, -- 1813-1855. Bible. -- Gospels -- Criticism, Narrative